(untitled) (De Legibus - Law Journal, 2021)
The court ruling addresses the matter of the State’s liability for damages arisen through the exercise of a judicial function, based on judiciary error. The ruling concluded that, as pre-requisite for said liability, unlawfulness must arise from the previous revocation of the detrimental decision by the competent jurisdiction. This revocation entails the judicial recognition of error with its characteristics in manifest when it is of law, or but grossly when it is of fact. The commentary grounds itself on the fact that the new legal regime (came into force January 1st 2020) did away with the distinction between decisions (purportedly) in breach of European Law and decision (allegedly) in breach of National Law, by making appealable for review any decision made final on the basis of (recognized) judiciary error.